2015
DOI: 10.1080/10942912.2015.1023399
|View full text |Cite
|
Sign up to set email alerts
|

Emulsifying and Foaming Properties of Protein Concentrates Prepared from Cowpea and Bambara Bean Using Different Drying Methods

Abstract: Effect of cabinet-drying (CD), vacuum-drying (VD) and freeze-drying (FD) methods on the surface hydrophobicity (H0), secondary structure, emulsifying and foaming properties of protein concentrates prepared from different cultivars of cowpea and Bambara bean was investigated.The VD method reduced H0, while freeze-dried concentrates presented high H0. The concentrates prepared by FD presented more β-sheet (40-43%) and less β-turn (19-24%) structures. Bambara bean protein concentrates prepared by FD presented hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 24 publications
(20 reference statements)
4
18
1
Order By: Relevance
“…The highest SH for sophia protein isolates prepared by UAE was observed (98.16 µg BPB), and the lowest for soy protein isolates as a reference (84.38 µg BPB) (Table 1). Significant differences in SH existed among extracted protein from different sources as reported (Mune and Sogi 2015;Tontul et al 2018). Therefore, the variations in surface hydrophobicity of extracted protein could be due to changes in protein structure caused by ultrasound.…”
Section: Surface Hydrophobicitymentioning
confidence: 87%
See 1 more Smart Citation
“…The highest SH for sophia protein isolates prepared by UAE was observed (98.16 µg BPB), and the lowest for soy protein isolates as a reference (84.38 µg BPB) (Table 1). Significant differences in SH existed among extracted protein from different sources as reported (Mune and Sogi 2015;Tontul et al 2018). Therefore, the variations in surface hydrophobicity of extracted protein could be due to changes in protein structure caused by ultrasound.…”
Section: Surface Hydrophobicitymentioning
confidence: 87%
“…Surface hydrophobicity (SH) is an important characteristic that influences protein functionality. Higher surface hydrophobicity means that protein isolates have stronger surfactant properties (Mune and Sogi 2015;Tontul et al 2018). It was found that the extract methods had different effects on the hydrophobicity surface of protein isolates from camelina and sophia seed meal.…”
Section: Surface Hydrophobicitymentioning
confidence: 99%
“…Studies reported variable results on the physicochemical properties (water and oil absorption capacities, gelation capacity, and foaming and emulsifying properties) of BGPI (105)(106)(107). The differences in functional properties of BGPI can be explained by several factors, including the amino acid composition (104), extraction method (38), extraction condition (108), and drying condition (109).…”
Section: Bambara Groundnut Protein Isolatementioning
confidence: 99%
“…Nevertheless, FD samples displayed the lowest content of β‐turn (15.80%). Mune and Sogi 43 also reported that FD contributed to less β‐turn structure (19–24%) of dried cowpea and bambara bean protein concentrates. This phenomenon might be a result of the detrimental effects caused by the high β‐sheet content in FD samples 42 …”
Section: Resultsmentioning
confidence: 94%